IMPLEMENTASI PLAY THERAPY BERBASIS AJARAN ISLAM UNTUK MENINGKATKAN KECERDASAN EMOSIONAL DAN SPIRITUAL ANAK USIA 5-6 TAHUN : Studi Kasus di Kober Alam Nur Cendekia, Kabupaten Cirebon - Wulan Cahya Rengganis; Muhammad Aziz Husnarrijal; Sri Maryati (Prodi Tasawuf dan Psikoterapi, Fakultas Agama Islam, Universitas Muhammadiyah Cirebon, 2025)
The background of this research is based on many cases of pre-school children (5-6 years old) committing aggressive acts both physically or non-physically (verbal) against their own friends, such as hitting, pushing, punching, saying harsh words, mocking and making fun of. One solution to this problem is for teachers to implement Islamic Play Therapy. With this research, teachers are expected to not only be able to educate intellectually, but most importantly be able to increase the emotional intelligence of children aged 5-6 years. This type of research is qualitative involving 23 children aged 5-6 years at Kober Alam Nur Cendekia, Cirebon Regency, West Java. Data collection methods used interviews, observation and documentation or a combination of the three (triangulation). One of the findings of this research, Play Therapy based on Islamic teachings, children are able to be tolerant, children are able to adapt socially, and children are able to manage their emotions.